2020
DOI: 10.1186/s12883-020-01957-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of acute ischemic stroke in hospitalized patients in Tibet: a retrospective comparative study

Abstract: Background Numerous studies on acute ischemic stroke (AIS) have been conducted at low-altitude regions, and the related findings have been used to guide clinical management. However, corresponding studies at high altitude are few. This study aimed to analyse the clinical characteristics of AIS patients at high-altitude regions through a hospital-based comparative study between Tibet and Beijing. Methods This study included the diagnoses of AIS patients from People’s Hospital of Tibet Autonomous Region (PHOTA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…This protective effect is stronger if the altitudes range from 2,000 to 3,500 m while residing above 3,500 m may be associated with an increased risk of developing stroke. It is consistent with the high stroke incidence reported in the epidemiological data of Tibet ( 13 ), as most of its cities or towns are located above 3,500 m. However, in this study, we found that this protection seems to be effective for lacunar infarction still, even when the patients reside at a very high altitude (Tibet). Angiogenesis or capillary remodeling in the brain may be the key reasons.…”
Section: Discussionsupporting
confidence: 92%
“…This protective effect is stronger if the altitudes range from 2,000 to 3,500 m while residing above 3,500 m may be associated with an increased risk of developing stroke. It is consistent with the high stroke incidence reported in the epidemiological data of Tibet ( 13 ), as most of its cities or towns are located above 3,500 m. However, in this study, we found that this protection seems to be effective for lacunar infarction still, even when the patients reside at a very high altitude (Tibet). Angiogenesis or capillary remodeling in the brain may be the key reasons.…”
Section: Discussionsupporting
confidence: 92%
“…Study 12: A hospital-based comparative study in Tibet and Beijing with 236 and 1021 patients, respectively, with acute ischaemic stroke published by Lu et al in 2020 demonstrated that patients diagnosed with acute ischaemic stroke located at 3650 m (Tibet) above sea level were younger than those who lived at 40 m (Beijing) above sea level (p<0.001); also, in Tibet, there was a higher proportion of cerebrovascular accidents in young adults, which may be associated with erythrocytosis. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Several anecdotal case reports and case series of people suffering from stroke-related disorders at high altitude have been published since the late 1800s 25. Despite this apparent relationship, very few well-conducted epidemiological studies have been conducted worldwide, and we have only included those studies that fulfilled our inclusion and exclusion criteria 14 15 20 21 26–36…”
Section: Resultsmentioning
confidence: 99%
“…A higher prevalence of acute ischemic stroke (>anterior circulation) was reported in younger Tibetan (Tibet 3650 m) compared to Chinese lowlanders (Beijing 40 m) and the authors suggested that erythrocytosis and hyperhomocysteinemia possibly contribute to these differences. 48 Another retrospective study reported that the first-ever acute ischemic stroke in Tibetan plateau residents were more severe and showed a larger infarct volume and less artherosclerotic factors, suggesting a prevailing risk related to the hypercoagulable state due to polycythemia (reduced blood flow and increase peripheral resistance) and an increased hypoxia-inflammatory response at HA. 44 First ever ischemic stroke due to polycythemia induced by chronic HH (>4000 m) exposure have been reported in Indian soldiers more frequently at high compared to low altitude (13.7 vs 1.05/1000).…”
Section: Literature and Research Methodsmentioning
confidence: 99%